Right Ovarian Ectopic Pregnancy in Young Woman with History of Right Salpingectomy; A Rare Case Report - Kataneh Kazemi; Mohsen Rakhsha; Seyed Hassan Seyed Sharifi; Mahboobeh Ghorbani (مجله دانشکده پزشکی اصفهان, 2018)
Background: Ovarian pregnancy is a rare form of ectopic pregnancy, and usually is diagnosed after complication. The most common risk factor for ovarian pregnancy is the use of the intrauterine devices (IUD).